TEACHING READING: STRATEGIES MOBILIZED IN THE UNDERSTANDING OF CARTOONS - Silva, Karine Tiepo da; Crestani, Lucian Maria; Guizelin Simoes Girotto, Cyntia Graziella [UNESP] (Fundacao Univ Tocantins, 2021)
This study focuses on the reading of cartoons.From the premise that identifying strategies mobilized in the reading may contribute to the process of teaching and learning and improve reading skills, we analyzed a cartoon to explain procedures mobilized to understanding the text. More specifically, we attempted to understand and explain what we look for and how we look at the text to (re)construct meanings. The corpus includes a cartoon by the cartoonist Iotti, published in Jornal Zero Hora, in 2018, and the analysis is based on studies about reading strategies, Bakhtinian precepts, and discursive semiotics. The study shows that understanding cartoons requires relevant knowledge to the social function of the genre, the immediate interdiscourse implicated in the reading, and the figurative network and theme manifested in the text, considering that the connections required to understanding are established thereof. It also indicates potential paths to reach deeper reading levels,which may help teachers and students in this process.
Keywords: Reading; Teaching Reading; Cartoon Genre